Influence of Quasi-Specific Sites on Kinetics of Target DNA Search by a Sequence-Specific DNA-Binding Protein - Kemme, Catherine A. (Biochemistry, 2015)
[Image: see text] Functions of transcription factors require formation of specific complexes at particular sites in cis-regulatory elements of genes. However, chromosomal DNA contains numerous sites that are similar to the target sequences recognized by transcription factors. The influence of such “quasi-specific” sites on functions of the transcription factors is not well understood at present by experimental means. In this work, using fluorescence methods, we have investigated the influence of quasi-specific DNA sites on the efficiency of target location by the zinc finger DNA-binding domain of the inducible transcription factor Egr-1, which recognizes a 9 bp sequence. By stopped-flow assays, we measured the kinetics of Egr-1’s association with a target site on 143 bp DNA in the presence of various competitor DNAs, including nonspecific and quasi-specific sites. The presence of quasi-specific sites on competitor DNA significantly decelerated the target association by the Egr-1 protein. The impact of the quasi-specific sites depended strongly on their affinity, their concentration, and the degree of their binding to the protein. To quantitatively describe the kinetic impact of the quasi-specific sites, we derived an analytical form of the apparent kinetic rate constant for the target association and used it for fitting to the experimental data. Our kinetic data with calf thymus DNA as a competitor suggested that there are millions of high-affinity quasi-specific sites for Egr-1 among the 3 billion bp of genomic DNA. This study quantitatively demonstrates that naturally abundant quasi-specific sites on DNA can considerably impede the target search processes of sequence-specific DNA-binding proteins.